The age of Štramberk-type limestone exotics from Kruhel Wielki vicinity in light of calpionellid biostratigraphy (Skole Nappe, Polish Outer Carpathians) - Woyda, Jan; Kowal-Kasprzyk, Justyna; Remin, Zbigniew (Acta Geologica Polonica, 2026)
The classic exposures of Štramberk-type exotic limestones in the Kruhel Wielki area (Gruszowa-Prałkowce Thrust Sheet, Skole Nappe) have been the subject of numerous studies on their stratigraphy and provenance. Previously, the age of the exotics was assumed to span the late Tithonian-Valanginian interval. However, calpionellid findings from the diverse exotic assemblages presented in this study allow the age of this interval to be narrowed to the late early Tithonian-early Berriasian. The uncertain presence of chitinoidellids in Štramberk-type limestones has been confirmed by the discovery of specimens belonging to the Family Chitinoidellidae. This research has allowed the distinguishing of three zones (Chitinoidella, Crassicollaria, and Calpionella), including six subzones (Dobeni, Boneti, Remanei, Massutiniana, Alpina, and Elliptica) based on representative calpionellid assemblages. Of the total number of 18 identified taxa, 8 were documented in this area for the first time. As a result of these studies, we were able to establish robust age correlations between material from different localities, which will be helpful for the further development of the carbonate platform model for the area.